2015
DOI: 10.1080/21645515.2015.1009342
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Epstein–Barr virus in Syrian women with breast cancer: A tissue microarray study

Abstract: Keywords: breast cancer, Epstein-Barr virus, invasive cancer, Syrian women Epstein-Barr virus (EBV) has been recently shown to be present in human breast cancer worldwide, which could play an important role in the initiation and progression of this cancer. In this regard, we aimed to explore the prevalence of EBV in 108 breast cancer tissues from Syrian women using polymerase chain reaction (PCR) and tissue microarray (TMA) analysis. We found that EBV is present in 56 (51.85%) of breast cancers samples. Additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
40
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 28 publications
0
40
1
1
Order By: Relevance
“…1) with one or more positive lymph nodes, in comparison with positive cases of EBV alone or HPVs alone as well as negatives cases for both, EBV and HPVs. 3,11,13 while, it is important to mention that EBV and HPVs positive cases were found to be low to intermediate grade IDC, respectively. In parallel, normal mammary tissue and epithelial cells, which were used as controls, were revealed negative for both EBV and HPVs.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…1) with one or more positive lymph nodes, in comparison with positive cases of EBV alone or HPVs alone as well as negatives cases for both, EBV and HPVs. 3,11,13 while, it is important to mention that EBV and HPVs positive cases were found to be low to intermediate grade IDC, respectively. In parallel, normal mammary tissue and epithelial cells, which were used as controls, were revealed negative for both EBV and HPVs.…”
mentioning
confidence: 99%
“…Additionally, we reported that the LMP1 expression is correlated with invasive breast cancer phenotype in more than 60% of breast cancer samples as opposed to »20% of in-situ cancer tissues. 3 Several other recent studies, including 3 from the Middle East, showed clearly that EBV is present in 30-50% of human breast cancer. [4][5][6][7][8] Overall, these studies demonstrate that EBV is present in human breast cancer; given the biological actions of EBV-derived onco-proteins, it is quite possible that it plays an important role in the initiation and/or progression of this malignancy.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…En este estudio se detectó la presencia de VEB en el 13.6% de nuestras pacientes con cáncer de mama, mientras que en aquellas con patología benigna se detectó ADN del VEB solo en una, representando el 4.5%. Este resultado se encuentra por debajo de los valores reportados en otros estudios realizados en el mundo, los cuales oscilan entre el 21 y el 55% de positividad para ADN del VEB, dependiendo del tipo de técnica empleada en la detección 4,19,40 . En los trabajos que emplearon algún tipo de PCR, al igual que en nuestro estudio, se detectaron bajas frecuencias de infección, como en el de Xue, et al 41 , quienes detectaron, mediante PCR específica de transcriptasa reversa para el gen BZLF1, el ARN viral en el 17% de los casos de cáncer de mama, o el trabajo de Yahia, et al 42 , quienes detectaron un 11% de positividad para ADN del VEB en los casos de cáncer de mama mediante PCR con iniciadores específicos para el gen EBNA-1.…”
Section: Discussionunclassified